Metagenomic comparison of bacterial diversity in kefir grains and liquid kefir - KURNIAWAN KURNIAWAN; TIANA MILANDA; SRI AGUNG FITRI KUSUMA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kurniawan, Milanda T, Kusuma SAF. 2025. Metagenomic comparison of bacterial diversity in kefir grains and liquid kefir. Biodiversitas 26: 6378-6388. This study compared the bacterial community composition of kefir grains and their corresponding whey from cow's milk fermentation using 16S rRNA gene-based metagenomic sequencing. Next-Generation Sequencing (NGS) analysis revealed 405 bacterial species in kefir grains and 294 in whey, with 118 species shared between both matrices. Lactobacillus kefiranofaciens dominated both environments, followed by Lactobacillus helveticus and Streptococcus thermophilus. Three key ecological patterns emerged. First, kefir grains exhibited higher microbial richness and diversity, reaffirming their role as the primary microbial reservoir during fermentation. Second, a core microbiome common to both matrices indicated functional continuity between solid and liquid phases, ensuring the stable transfer of fermentative consortia. Third, distinct community structures in the liquid phase were shaped by ecological filtering, where oxygen-tolerant taxa such as acetic acid bacteria gained relative dominance. The study highlights the ecological complexity and regional uniqueness of Indonesian artisanal kefir, which showed greater microbial richness than most reported global datasets. The results provide insights for enhancing food safety, optimizing probiotic formulations, microbial succession, core community dynamics, and potential probiotic resources for food biotechnology. These findings underscore the ecological complexity and regional distinctiveness of Indonesian artisanal kefir, which exhibited higher microbial richness than most global reports.